Comprehensive insights on environmental adaptation strategies in Antarctic bacteria and biotechnological applications of cold adapted molecules - Ramasamy, Kesava Priyan; Mahawar, Lovely; Rajasabapathy, Raju; Rajeshwari, Kottilil; Miceli, Cristina; Pucciarelli, Sandra (Frontiers in Microbiology, 2023)
Climate change and the induced environmental disturbances is one of the major threats that have a strong impact on bacterial communities in the Antarctic environment. To cope with the persistent extreme environment and inhospitable conditions, psychrophilic bacteria are thriving and displaying striking adaptive characteristics towards severe external factors including freezing temperature, sea ice, high radiation and salinity which indicates their potential in regulating climate change's environmental impacts. The review illustrates the different adaptation strategies of Antarctic microbes to changing climate factors at the structural, physiological and molecular level. Moreover, we discuss the recent developments in “omics” approaches to reveal polar “blackbox” of psychrophiles in order to gain a comprehensive picture of bacterial communities. The psychrophilic bacteria synthesize distinctive cold-adapted enzymes and molecules that have many more industrial applications than mesophilic ones in biotechnological industries. Hence, the review also emphasizes on the biotechnological potential of psychrophilic enzymes in different sectors and suggests the machine learning approach to study cold–adapted bacteria and engineering the industrially important enzymes for sustainable bioeconomy.